Antidiabetic and antioxidant activities of Gracilaria verrucosa extract: In vitro and in vivo assessment - Prasasty, Vivitri Dewi; Hutagalung, Rory Anthony; Vianney, Michele (Edelweiss Applied Science and Technology, 2025)
The increasing prevalence of diabetes mellitus and limitations of conventional treatments have intensified the search for natural remedies. This study evaluated the antidiabetic and antioxidant activities of red seaweed Gracilaria verrucosa extracts through in vitro and in vivo assessments. Phytochemical screening revealed alkaloids, triterpenoids, saponins, and phenolics. Three extraction methods using ethanol, distilled water, and warm distilled water were employed, with warm distilled water yielding the highest extraction (7.56%). Gas Chromatography-Mass Spectrometry analysis identified n-hexadecanoic acid as the predominant compound in ethanolic (37.87%), distilled water (12.33%), and warm distilled water extracts (11.42%). For antidiabetic activity, α-amylase inhibitory assay using 3,5-dinitrosalicylic acid method demonstrated that warm distilled water extract exhibited the strongest inhibition (IC₅₀ = 45,117.16 ppm). Antioxidant evaluation using 2,2-diphenyl-1-picrylhydrazyl radical scavenging showed ethanolic extract possessed the most potent activity (IC₅₀ = 21,730.07 ppm). In vivo studies utilized alloxan-induced diabetic male mice (Mus musculus L.) treated orally with G. verrucosa extracts (300 mg/kg BW) for 14 days. Results demonstrated that both ethanolic and warm distilled water extracts significantly reduced blood glucose levels in diabetic mice (initial fasting blood glucose >126 mg/dL) to below 100 mg/dL. These findings suggest G. verrucosa extract has considerable potential as a natural therapeutic agent for diabetes mellitus management.